Development of a low-cost system for the measurement of dynamic equilibrium in humans - Silva, Marcelo Guimarães [UNESP]; Martins, Marcelo Sampaio [UNESP]; Tupinambá, Walter Luis Medeiros [UNESP]; Tomazini, José Elias [UNESP] (Springer Nature, 2024)
Introduction: The maintenance of balance and body orientation during stance is essential for performing different activities. The aim of this study was to describe the development of a non-commercial, low-cost device to measure human dynamic equilibrium through both biomechanical parameters: Ground Reaction Force (GRF) and displacement of the Center of Pressure (COP). Additionally, the study aimed to validate and assess the practical applicability of this device, designed for scientific research purposes. Methods: The acquisition of contact forces data of supporting foot was obtained from a force platform developed according to International Standards of Measurement. This platform was constructed for approximately one-tenth of the cost of commercial platforms. Results: The device calibration showed an adequate connectivity, linearity, and reliable measurement of the variables proposed in this study, being suitable for studies aiming to assess the balance in humans. An experimental study was conducted to verify the applicability of the device, through measuring COP and GRF variables. Conclusion: Based on the study results, we believe that this low-cost and effective device can be used to measure postural control and balance in clinical and sports experiments. However, further studies are required to validate this device by comparing it with other stabilometric devices.
Keywords: Biomechanical parameters; Dynamic equilibrium; Low-cost equipment; Postural control